A polarity-sensitive fluorescent probe based on a difluoroboron derivative for monitoring the variation of lipid droplets. (10th November 2021) - Wang, Hui; Hu, Lei; Shen, Shuting; Yu, Kun; Wang, Yaxuan
Abstract : We design LD-L, a polarity-sensitive fluorescent probe, which can specifically detect lipid droplets and monitor variations in their number. Abstract : The detection of lipid droplet (LD) variation is an important and challenging work in biological research. Herein, a novel fluorescent dye, LD-L, a difluoroboron derivative, was constructed and systematically investigated. It was found that LD-L is polarity sensitive and can quantitatively analyze the polarity in solvent mixtures. Interestingly, LD-L can specifically detect LDs and monitor variations in their number. Moreover, given the excellent biocompatibility, favorable photostability and tissue penetrability, we believe that probe LD-L has great potential in disease diagnosis.